The Effect of School Principles Motivation in Efforts to Improve Teacher Performance at Integrated Islamic Elementary School - Dian, Dian; Trisna, Muhammad Yogi; Huda, Nenden Najiatul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aimed to determine the effect of the principal's motivation on teacher performance at Integrated Islamic elementary school Matahati Bandung. The method used in this research is a quantitative approach with the associative method. The population in this study amounted to 30 teachers and was taken as a sample of 30 teachers with the research instrument in the form of a questionnaire. The result of this study; 1) the regression coefficient value is 1.006. So every one percent of motivation from the principal will improve teacher performance by 1,006. Thus the motivation of the principal has a positive effect on the teacher's performance. Square R-value = 0.610, hence the effect value is 61%. Thus, the provision of motivation from the principal can improve teacher performance by 60%; 2) the principal is significantly influential in efforts to improve teacher performance in SDIT Matahati with the magnitude of the influence by 90.6%; 3) Principals on teacher influence by 88.6%. The study results imply that the principal's motivation is a factor that can affect teacher performance.